Comportamento de compra da tecnologia para controle do Arroz Vermelho - Koehler, Evandro (Universidade do Vale do Rio dos Sinos, 2011)
This study aims to investigate the behavior of purchasing the technology for red rice control, and the importance of personal values attributed to the choice of technology. Based on this, this monograph was developed based on literature on consumer behavior. Its importance is due to the need of the professional manufacturer of technology, understand consumer behavior in order to increase sales and increase market share in irrigated rice. Red rice is the main invasion of rice crops in Rio Grande do Sul Clearfield ® technology was developed by BASF, and one year from the launch farmers began using this tool in an irresponsible manner without provenance seed planting and applying products not registered for the system. As a result, a search theoretical model of factors influence marketing, social and cultural as well as understanding the theoretical model of the process of buying technology, it becomes important to investigate the reasons why farmers in the region of rice Cachoeira do Sul using an inadequate management control red rice. To obtain measurable data on consumer behavior when buying products, it was necessary to apply a quantitative research through personal research to farmers in this region. The results showed that cultural values have had the most extensive and profound influence on consumer behavior. The perceptions and values are different between social classes, age, length of experience with irrigated rice fields, demographics, and schooling. The influences of marketing showed recognition technology, but the price charged by it is still very high. Social factors have underlined the importance of reference groups and family in the final purchase decision.
Keywords: Comportamento; Consumidor; Arroz Vermelho; Sistema de Produção Clearfield®; Arroz; Behavior; Consumer; Red Rice; Clearfield ® Production System; Rice